2005
DOI: 10.1093/toxsci/kfi270
|View full text |Cite
|
Sign up to set email alerts
|

Research Strategies for Safety Evaluation of Nanomaterials, Part I: Evaluating the Human Health Implications of Exposure to Nanoscale Materials

Abstract: Nanotechnology has the potential to dramatically improve the effectiveness of a number of existing consumer and industrial products and could have a substantial impact on the development of new products ranging from disease diagnosis and treatment to environmental remediation. The broad range of possible nanotechnology applications could lead to substantive changes in industrial productivity, economic growth, and international trade. A continuing evaluation of the human health implications of exposure to nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(89 citation statements)
references
References 11 publications
0
87
0
2
Order By: Relevance
“…1,2 These smaller particles meet the definition of manufactured nanoparticles, described as any synthetic material with one or more dimension less than 100 nm. 3 Although TiO 2 particles with diameter >100 nm are considered toxicologically inert, 1 it has been suggested that the greater relative surface area of nanosized particles may cause them to be more biologically active and increase their toxicity. 4 TiO 2 nanomaterials that enter the environment during their production, use, or disposal may be deposited in soil or accumulate in sewage treatment plant sludge that may subsequently be applied to soil.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1,2 These smaller particles meet the definition of manufactured nanoparticles, described as any synthetic material with one or more dimension less than 100 nm. 3 Although TiO 2 particles with diameter >100 nm are considered toxicologically inert, 1 it has been suggested that the greater relative surface area of nanosized particles may cause them to be more biologically active and increase their toxicity. 4 TiO 2 nanomaterials that enter the environment during their production, use, or disposal may be deposited in soil or accumulate in sewage treatment plant sludge that may subsequently be applied to soil.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As smaller size nanoparticles increase reactivity in cells (Thomas and Sayre, 2005) and even more, nanoparticles can bind to DNA or amino acid (Nel et al, 2006), it seems that they are often much more reactive than their bulk material As recent reports suggest that nanoparticles may penetrate into cell membrane and effect DNA condition, it is necessary to assay possible cytotoxic and genotoxic risk. Three different sizes of magnetic nanoparticle silica (MNP@SiO 2 ) (50, 100 and 200 nm diameter) were tested for cytotoxicity and DNA damage using L5178Y cell.…”
Section: Introductionmentioning
confidence: 99%
“…And its biological activities including antiviral, antioxidant, and chemotactic activities have also been tested on various fullerene-based compounds [1][2][3][4]. In recent years, some publications and reports have raised the health and safety concerns about the production and application of nanoparticles, especially in areas of exposure monitoring, personal use, environmental fate, and transport [5][6][7][8][9][10][11]. Although early studies showed low toxicity of the C 60 molecule itself [12], some recent studies found that C 60 is toxic to the biological systems.…”
Section: Introductionmentioning
confidence: 99%